COMPLEX GEMOLOGICAL RESEARCH OF NEW TYPES OF TREATED AMBER - Belichenko, O.; Ladzhun, J. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Complex gemological research of heat-treated amber that appeared on global market recently was conducted. Amber like that was artificially treated, which is indicated by evidence of treatment, such as large amounts of microscopical gas bubbles. The goal of treatment is to create fully opaque amber which is popular at Chinese market. Samples of unnaturally pink-orange color were examined as well. Primary gemological characteristics: refractive index, specific gravity, LWUV and SWUV fluorescence were studied. Microscopical examination of surface and gas inclusions and study of IR-specters of treated samples were conducted. Obtained results indicate that the samples underwent similar artificial treatment, diagnostic feature of which is the significant amount of microscopical gas inclusions, whose size, shape and distribution differ from naturally occurring ones. It can be assumed that amber like this is obtained via heat treatment in autoclave under pressure with addition of water or water with dye. It was determined that gemological characteristics of studied samples are in range of those typical for succinite. IRspecters of all studied samples, both pale-yellow and pink-orange ones, have specific configuration, typical for succinite. It was established that the primary diagnostic method is the detailed examination of surface structure for characteristic gas bubbles.